Structural Features of an OR37 Glomerulus: A Comparative Study - Maier, Anna-Maria; Breer, Heinz; Strotmann, Jörg (Frontiers in Neuroanatomy, 2017)
In the olfactory bulb a sophisticated neuronal network mediates the primary processing of sensory information and extensive investigations over the past decades have greatly improved our understanding of the morphology and neuronal organization of the olfactory bulb. However, efforts have mostly been focused on the different radial layers, typical for the olfactory bulb and little attention has been paid to individual odorant receptor specific glomeruli, the first relay station of sensory information. It has been assumed that glomeruli processing odorant information out of different contextual fields might require accordingly specialized neuronal networks. In this study, we have analyzed and compared the structural features as well as cell types in the periglomerular region of three odorant receptor specific glomeruli. The investigations were focused on glomeruli of the receptor type OR37A, a member of the unique OR37 subsystem, in comparison to glomeruli of OR18-2, a class I odorant receptor and OR256-17, a class II receptor. Each of the odorant receptor types is known to be activated by distinct odorants and their glomeruli are located in different regions of the bulb. We found significant differences in the size of the glomeruli as well as in the variability of the glomerulus size in individual mice, whereby the OR37A glomeruli featured a remarkably stable size. The number of cells surrounding a given glomerulus correlated strongly with its size which allowed comparative analyses of the surrounding cell types for individual glomeruli. The proportion of periglomerular cells labeled by NeuN as well as putative GABAergic neurons labeled by GAD65 was quite similar for the different glomerulus types. However, the number of cells expressing distinct calcium-binding proteins, namely parvalbumin, calbindin or calretinin varied significantly among the three glomerulus types. These data suggest that each odorant receptor specific glomerulus type may be surrounded by a unique network of periglomerular cells.